Financial innovation, financial development, and economic growth: Empirical evidence on Sub-Saharan African countries - Emna, Makni; Hanene, Ezzine; Ines, Abdelkefi; Aida, Smaoui (International Journal of Management and Sustainability, 2025)
This study investigates the relationship between financial innovation, financial development, and economic growth in eight Sub-Saharan African countries from 2011 to 2021. Using panel data analysis, the study incorporates financial innovation indicators such as internal credit to the private sector, openness to international trade, gross capital formation, and information and communication technology, while financial development is measured through the size of financial intermediaries and stock market capitalization. The findings reveal that internal credit, capital formation, and stock market development do not significantly influence economic growth in the region, whereas information and communication technology and openness to trade show a positive impact. These results suggest that technology-driven and trade-related financial innovations play a more critical role in driving economic growth than traditional financial metrics. Accordingly, the study provides practical implications for policymakers in Sub-Saharan Africa, emphasizing the need to support financial innovation through ICT investment and trade openness to enhance the efficiency of financial markets and stimulate sustainable economic development.